Changes in renal medullary pO(2) during water diuresis as evaluated by blood oxygenation level–dependent magnetic resonance imaging: Effects of aging and cyclooxygenase inhibition - Prasad, Pottumarthi V. (1999)
BACKGROUND: Hypoxia of the renal medulla has been implicated in the development of renal injury, particularly acute renal failure, and its regulation in humans may therefore be relevant to certain renal disorders. Changes in oxygenation of the renal medulla can now be monitored noninvasively with blood oxygenation level–dependent (BOLD) magnetic resonance imaging (MRI). Using this method, water diuresis has been shown to improve medullary oxygenation in young persons. Urinary excretion of prostaglandin E(2) (PGE(2)) likewise increases during water diuresis in younger but not in older people. We used BOLD MRI to measure the effects of aging and of inhibiting prostaglandin synthetase on the renal response to water diuresis in healthy human subjects. METHODS: Nine younger (25 to 31 years) and nine older (59 to 79 years) female volunteers were studied with BOLD MRI during antidiuresis in the postabsorptive state and during water diuresis. Simultaneously, urinary excretion of PGE(2) was determined. PG synthetase was inhibited by administering ibuprofen. RESULTS: Renal medullary oxygenation, initially low, greatly improved during diuresis in younger subjects, whereas PGE(2) excretion increased. In older women, however, water diuresis elicited no change in oxygenation of renal medulla or PGE(2) excretion. Ibuprofen inhibited excretion of PGE(2) and blocked the increase in medullary oxygenation normally produced by water diuresis in the young. CONCLUSIONS: The increase in oxygenation of the renal medulla accompanying water diuresis depends on PGE(2) synthesis. Attenuation of renal PGE(2) synthesis in older people is probably responsible, at least in part, for the loss of the ability to improve medullary oxygenation that younger subjects possess. Inability to improve renal medullary oxygenation might predispose to hypoxic renal injury in older patients.